PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN KONSUMEN MEMBELI TIKET PESAWAT ONLINE DI TRAVELOKA - Abdul, Sadam; Nasution, Ute Chairuz; Mulyati, Awin (Jurnal Dinamika Administrasi Bisnis, 2017)
With the high demand of society will be the use of flight services of late, then this growing competition on the companies of a kind. Advanced in the transport sector can also create a new business that appears is the travel in the sense that as the agent of the cooperation with the providers of transportation airlines. The emergence of several travel services makes this society will be easier to get airplane tickets with cheap price and quickly. With high competition then it is hoped that each of the company tried to meet the needs of the customer and consumer satisfaction are met. This research wants to know the influence of the quality of service and a promotion to the decision of the consumers buy airplane ticket online at traveloka"based on the analysis and the discussion that has been done in this research can be obtained the conclusion with the variable quality of service and the promotion of significant effect against the decision of the consumers buy airplane ticket online at Traveloka.in prove with test Fkeyword: service quality, promotion and customer satisfaction